Comparative Antibacterial Activity of Tannin-Enriched Aqueous Extracts of Citrus limon and Capparis spinosa Against Bacterial Isolates Recovered from Poultry Meat - Ahmed Abdulqader, Omar (American Journal of Biology and Natural Sciences, 2026)
The antibacterial activity of tannin extracts isolated from Citrus limon and Capparis spinosa against bacterial isolates recovered from poultry meat was studied in this research. VITEK 2 Compact system to determine eight bacterial species and agar well diffusion method on Mueller–Hinton agar at five extract concentrations (100, 75, 50, 25, and 12 mg/mL). Both extracts showed inhibitory activity, but Citrus limon consistently displayed a larger inhibition zone than Capparis spinosa. The maximum effective activity of Citrus limon was against Providencia alcalifaciens (27.23 ± 0.25 mm at 100 mg/mL), while the maximum effective activity of Capparis spinosa was observed against Proteus mirabilis (18.07 ± 0.12 mm at 100 mg/mL). Inhibition zone diameters were significantly influenced by extract type, concentration, and their interaction, as determined by statistical analyses. These results suggest that plant extracts, such as Citrus limon, which are high in tannins, can improve their viability and may be a potential natural antibacterial agent for the preservation of poultry. However, further studies (phytochemical characterization, MIC/MBC determination, and validation in real food storage conditions) are required to show the practical applicability of these substances in food safety systems.